Satellite communications - Roddy, Dennis, 1931- (New York : McGraw-Hill, 2006)
Annotation Master the fundamentals of satellite communicationsHighly regarded for more than a decade as both a teaching text and professional tutorial, this classic guide to satellite communications has been revised, updated, and expanded to cover global wireless applications, digital television, and Internet access via satellite. In-depth, textbook-style coverage combined with an intuitive, low-math approach makes this book particularly appealing to the wireless and networking markets New to this edition: Global wireless services, including 3G; Antenna Options, Error Coding.
Overview of satellite systems -- Orbits and launching methods -- The geostationary orbit -- Radio wave propagation -- Polarization -- Antennas -- The space segment -- The earth segment -- Analog signals -- Digital signals -- Error control coding -- The space link -- Interference -- Satellite access -- Satellites in networks -- Direct broadcast satellite (DBS) television -- Satellite mobile and specialized services.
Includes bibliographical references and index.
1
Keywords: Artificial satellites in telecommunication